(untitled) (Research, Society and Development, 2020)
This article aims to reveal the role of feedback in peer review based on the development of activities carried out with undergraduate students, in three subjects of a Mathematics Degree Course. Theoretically, this research was supported by theories related to formative evaluation, peer evaluation and feedback. Methodologically, it is a qualitative-exploratory research, whose data were collected through an electronic questionnaire (Google forms), with twelve students who attended the subjects of Mathematics Education Seminars, Mathematics Teaching Practice I and II. This questionnaire was collected eight months after the end of the courses. Among the results achieved, it can be detach that there are signs that evidence the occurrence of a formative evaluation; students were able to identify and analyze what was learned and what still needed to be improved; the focus of the evaluation was to promote learning; feedback can help students to regulate their learning; especially when performed orally, by everyone, immediately after work and in writing, by the teacher.